The Free-Living Stage Growth Conditions of the Endophytic Fungus Serendipita indica May Regulate Its Potential as Plant Growth Promoting Microbe - Dias, Teresa; Pimentel, Vívian; Cogo, Antônio Jesus Dorighetto; Costa, Raquel; Bertolazi, Amanda Azevedo; Miranda, Camila; de Souza, Sávio Bastos; Melo, Juliana; Carolino, Manuela; Varma, Ajit; Eutrópio, Frederico; Olivares, Fábio Lopes; et al. (Frontiers in Microbiology, 2020)
Serendipita indica (former Piriformospora indica) is a non-obligate endophytic fungus and generally a plant growth and defense promoter with high potential to be used in agriculture. However, S. indica may switch from biotrophy to saprotrophy losing its plant growth promoting traits. Our aim was to understand if the free-living stage growth conditions (namely C availability) regulate S. indica’s phenotype, and its potential as plant-growth-promoting-microbe (PGPM). We grew S. indica in its free-living stage under increasing C availabilities (2-20 g L-1 of glucose or sucrose). We first characterized the effect of C availability during free-living stage growth on fungal phenotype: colonies growth and physiology (plasma membrane proton pumps, stable isotopic signatures and potential extracellular decomposing enzymes). The effect of the C availability during the free-living stage of the PGPM was evaluated on wheat. We observed that C availability during the free-living stage regulated S. indica’s growth, ultrastructure and physiology, resulting in two distinct colony phenotypes: compact and explorer. The compact phenotype developed at low C, used peptone as the major C and N source, and displayed higher decomposing potential for C providing substrates; while the explorer phenotype developed at high C, used glucose and sucrose as major C sources and casein and yeast extract as major N sources, and displayed higher decomposing potential for N and P providing substrates. The C availability, or the C/N ratio, during the free-living stage left a legacy to the symbiosis stage, regulating S. indica’s potential to promote plant growth: wheat growth promotion by the explorer phenotype was ± 40% higher than that by the compact phenotype. Our study highlights the importance of considering microbial ecology in designing PGPM/biofertilizers. Further studies are needed to test the phenotypes under more extreme conditions, and to understand if the in vitro acquired characteristics persist under field conditions.